Sequence variants with large effects on cardiac electrophysiology and disease - Kristjan Norland (Nature Portfolio, 2019)
Aberrant morphology of the QRS complex in an electrocardiogram can be associated with cardiac morbidity and mortality. Here, the authors perform genome-wide association studies for ten measures of the QRS complex in 81,192 individuals and find 86 previously unreported loci that associate with at least one parameter.